Non-destructive determination of collagen fibril width in extruded collagen fibres by piezoresponse force microscopy. (13th September 2017) - Bazaid, Arwa; Neumayer, Sabine M; Sorushanova, Anna; Guyonnet, Jill; Zeugolis, Dimitrios; Rodriguez, Brian J
Abstract: Extruded collagen fibres are a promising platform for tissue engineering applications. Ensuring that the functional properties of the engineered tissues possess similar structural properties as native tissues is important for biomedical applications. Advanced imaging tools including scanning electron microscopy (SEM) and atomic force microscopy (AFM) have revealed the structural features of collagen fibrils within such fibres; however, these techniques often require modification steps that can alter the sample in the process. Here, lateral piezoresponse force microscopy (LPFM), which is sensitive to the polar orientation of piezoelectric collagen fibrils, is demonstrated as a promising tool to assess the width of individual fibrils and moreover map their organisation and polar orientation without altering the sample. Within the fibres studied, the collagen fibrils showed a highly anisotropic arrangement with preferred alignment along the length of the fibre. Fibril widths of 74 ± 18 nm and 73 ± 19 nm in untreated and bleached fibres, respectively, were measured from LPFM amplitude images. These values agreed with values from SEM (70 ± 10 nm) and AFM (71 ± 19 nm) measurements that could only be obtained from bleached fibres.